Monitoring concentration and lipid signature of plasma extracellular vesicles from HR+ metastatic breast cancer patients under CDK4/6 inhibitors treatment - Mathilde Richard; Rosalie Moreau; Mikaël Croyal; Laurent Mathiot; Jean‐Sébastien Frénel; Mario Campone; Aurélien Dupont; Julie Gavard; Gwennan André‐Grégoire; Laëtitia Guével (Journal of Extracellular Biology, 2024)
Abstract Extracellular vesicles (EVs) are cell‐derived small membrane structures that transport various molecules. They have emerged as potential circulating biomarkers for monitoring responses to cancer therapies. This study aimed to comprehensively characterize plasma‐carried EVs in hormone receptor‐positive (HR+) metastatic breast cancer (MBC) patients treated with first‐line CDK4/6 inhibitors (iCDK4/6) combined with endocrine therapy. MBC patients were classified into three groups based on their response to therapy: resistant, intermediate or sensitive. In a prospective cohort, we monitored the concentration of circulating EVs, analyzed their lipid signature and correlated these factors with treatment response. To facilitate the translation of EV research to clinical practice, we established a three‐step procedure: (1) EVs were isolated from plasma using semi‐automatized size exclusion chromatography (SEC); (2) EV concentration, termed vesiclemia, was determined by drop counting via interferometric light microscopy (ILM); and (3) EV lipid composition was analyzed by mass spectrometry. ILM‐based vesiclemia values were highly fluctuating upon iCDK4/6 treatment, while early increase associated with accelerated progression. Of note, vesiclemia remained a steady parameter over a 1‐year period in age‐matched healthy women. Additionally, analysis of the EV cargo unveiled a distinct sphingolipid profile, characterized by increased levels of ceramides and sphingomyelins in resistant patients within the first 2 months of treatment. Based on 16 sphingolipid species, sensitive and resistant patients were correctly classified with an overall accuracy of 82%. This specific sphingolipid pattern was exclusively discernible within EVs, and not in plasma, highlighting the significance of EVs in the early prediction of individual responses to iCDK4/6 and disease progression. Overall, this study provides insights of the longitudinal characterization of plasma‐borne EVs in both a healthy group and HR+ MBC patients under iCDK4/6 therapies. Combined vesiclemia and EV sphingolipid profile emphasize the promising potential of EVs as non‐invasive biomarkers for monitoring early treatment response.